Effect Of Environmental Concern, Attitude, Subjective Norms, Perceived Behavioral Control And Availability On Purchase Of Green Skincare Products With Intention To Purchase As A Mediation Variable - Tommy Setiawan Ruslim; Yeni Kartika; Claudia Gita Hapsari (Universitas Mercu Buana, 2022)
The purpose of this study was to examine the effect of environmental concern, attitude, subjective norms, perceived behavioral control and availability on the purchase of green skincare products in Jakarta with intention to purchase as a mediating variable. Data analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM). This study used a purposive sampling method by distributing online questionnaires via google form to 180 respondents. The results showed that environmental concern, attitude and perceived behavioral control had a positive and significant effect on the intention to purchase green skincare products, while subjective norms and availability did not significantly affect the intention to purchase green skincare products. Intention to purchase green skincare products has a positive and significant influence on the purchase of green skincare products. Intention to purchase green skincare products can mediate the effect of environmental concern and attitude towards purchasing of green skincare products.